Complexos metálicos de rutênio: propriedades fotoquímicas e ação antimicrobiana - Barrozo, Auridéia Possidônio de Sousa (2022)
Ruthenium complexes have stood out for presenting relevant biological applications, including the possibility of being used as prodrugs that can be photoactivated. In this work, three ruthenium complexes were synthesized: cis-[Ru(bpy)2(SO3)(CO)] (I); cis-[Ru(bpy)2(Met)](PF6)2 (II), where bpy = 2,2'-bipyridine and Met = methionine; ct-[RuCl(NO)(dppb)(4,4'-Mebpy)](PF6)2 (III), where dppb = 1,4-bis(diphenylphosphino) and Mebpy = 4,4'-dimethylbipyridine. In addition to having Ruthenium as a metallic center, these complexes have ligands with pharmacological potential that make them interesting for application as metal-pharmaceuticals. The characterization was performed using spectroscopic techniques (electron spectroscopy in the ultraviolet and visible region, vibrational spectroscopy in the infrared region and 1H and 13C Nuclear Magnetic Resonance), cyclic voltammetry and X-ray diffraction. Thinking about the pharmacological actions performed by carbon monoxide (CO) and nitric oxide (NO), among them, the bacteriostatic and bactericidal properties. Regarding complex II, studies indicate that amino acids, such as methionine, can be drug carriers to specific targets such as cancer cells and bacteria, which motivated the synthesis and characterization of this compound. The complexes were subjected to photochemical studies with ultraviolet and visible light. The irradiations of the complexes were monitored by spectrophotometric, chromatographic and electrochemical techniques. The release of CO was confirmed by assays with myoglobin and cyclic voltammetry with Hemin. NO release was monitored by spectrophotometric technique. Furthermore, the appearance of an anodic process at 0.8 V of the irradiated solution of the complex, confirms the release of NO. In the case of complex II, the verification of the release of the methionine ligand was made through vibrational spectroscopy in the infrared region. All complexes were tested against strains of Gram-positive and Gram-negative bacteria, however, complex I did not show bactericidal and bacteriostatic activity. Complexes II and III showed antimicrobial action only against Gram-positive bacteria, with emphasis on complex III which showed a minimum inhibitory concentration (MIC) value of 7.8 µg/mL against Staphylococcus aureus (ATCC 25923) and Staphylococcus epidermidis (ATCC 12228). Thus, the results show the development of new complexes with pharmacological potential benefited by irradiation with visible light.